Peppermint and Ginger Aromatherapy for Managing Nausea and Vomiting During Chemotherapy - Fenny Maryani; Yani Sofiani; Rizki Nugraha Agung; Fitrian Rayasari; Dian Noviati Kurniasih (Indonesian Journal of Global Health Research, 2025)
Nausea and vomiting are common side effects experienced by breast cancer patients undergoing chemotherapy. Complementary therapies, such as peppermint and ginger aromatherapy, have been widely studied as alternatives to relieve these symptoms. However, the effectiveness of each type of aromatherapy needs further evaluation. Objective: This study aims to analyze the effectiveness of peppermint and ginger aromatherapy in reducing nausea and vomiting in breast cancer patients undergoing chemotherapy. Methods: A Quasi-Experimental design was used with 28 breast cancer patients at Husada Hospital Jakarta, divided into two groups: peppermint and ginger. Nausea and vomiting levels were measured before, 2 hours, and 6 hours after chemotherapy and analyzed using ANOVA Repeated Measures and Independent T-Test. Results: The results showed that both peppermint and ginger aromatherapy significantly reduced nausea and vomiting after chemotherapy (p < 0.05). However, at 6 hours after chemotherapy, the peppermint group had lower average nausea and vomiting scores compared to the ginger group (6.57 vs. 10.29, p = 0.036). This indicates that peppermint is more effective than ginger in reducing nausea and vomiting after chemotherapy. Conclusion: Both peppermint and ginger aromatherapy are effective in reducing nausea and vomiting in breast cancer patients undergoing chemotherapy. However, peppermint showed higher effectiveness compared to ginger at the 6-hour post-chemotherapy time point. Future research could explore the combination of peppermint and ginger aromatherapy to enhance effectiveness in reducing nausea and vomiting in breast cancer patients.